Inadequate Antenatal Care Visits and Risks of Infant Mortality in Rural District: Kunjungan Antenatal Care yang tidak Memadai dan Risiko Kematian Bayi di Daerah Pedesaan - Sukma Rahayu; Toha Muhaimin (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2022)
Introduction: Infant Mortality Rate (IMR) in Indonesia has decreased over the last fifteen years, but still left behind from other South-East Asia countries. One of the efforts to reduce IMR is antenatal care. However, there are disparity of antenatal care coverage between rural and urban area. Objective: This study aimed to determine the effect of antenatal care on infant mortality in rural district in Indonesia. Methods: The quantitative study used cross-sectional secondary data from Indonesia Demographic Health Survey 2017 with a total sample of 7.551 most recent born infant in 2012-2017 from women with childbearing age who’s live in rural district. Logistic regression multivariate analysis was used to determine the effect of antenatal care and infant mortality. Results: The results show that antenatal care reduce risk of infant mortality. Infants whose mothers had 1-3 antenatal care visits (OR = 3; 95% CI = 1.6 – 5.3) and no antenatal care visits (OR = 3; 95% CI = 1.6 – 5.5) had higher odds compared to infants whose mother had 4 or more antenatal care visits after controlled by social-economic status, maternal occupation, parity, and tetanus immunization. Conclusions: Empowering community empowerment with the help of community health workers and midwives is needed to target women with low social economic status. Studies and regulations for pregnant and lactating women at work also needed to reduce infant mortality. Further research involving quality of antenatal care and more covariates variables might be carried out.